DEVELOPING ENGLISH READING MATERIALS FOR STUDENTS OF CERDAS MURNI ISLAMIC JUNIOR HIGH SCHOOL - Diah Ayu Nanda; Johan Sinulingga; Morada Tetty (Universitas Negeri Medan, 2017)
This study aimed to develop English reading materials needed for students of Cerdas Murni Islamic Junior High School through Authentic Material Approach (AMA).The objective of this study was to develop relevant English reading materials to the needs of Cerdas Murni Islamic Junior High School students especially eight grade . This study was conducted by Research and Development (R&D) design through six phases: 1) Collecting data, 2) Analyzing data, 3) Developing new materials, 4) Validating product 5) Revising materials, 6) final product. The data of this research were from the existing materials, syllabus, students’ questionnaire, and the teachers’ interview. The result of this research showed that the existing materials were not suitable to the Islamic school students’ needs.. Therefore, new English reading materials were developed through Authentic Material Approach (AMA) principles in order to meet the Islamic students’ needs. Furthermore, developing English reading materials were recount text. Recount text expose personal recount “Tarawih Changed his Life and the biographical recounts of Prophet Muhammad SAW and Shalahuddin Al-Ayyubi”. The English reading materials were validated by English teacher and English lecturer. Both of them agreed that new English reading materials were suitable with the Islamic school students’ needs. Key Words: English reading materials, Islamic junior high school, Research and Development (R&D)